Mutational analysis of fructose-1,6-bis-phosphatase FBP1 indicates partially independent functions in gluconeogenesis and sensitivity to genotoxic stress - Ali Ghanem; Ana Kitanovic; Jinda Holzwarth; Stefan Wölfl (Microbial Cell, 2017)
Fructose-1,6-bisphosphatase (FBP1) is a key enzyme in the evolutionary conserved pathway of gluconeogenesis. We had shown in an earlier study that FBP1 is involved in the response and sensitivity to methyl-methanesulfonate (MMS)-induced DNA damage in yeast. In the work presented here we performed an alanine screen mutational analysis of several evolutionary conserved amino acid residues of FBP1, which were selected based on conserved residues and structural studies of mammalian and yeast homologues of FBP1. Mutants were examined for enzymatic activity, and yeast cells expressing these mutants were tested for growth on non-fermentable and MMS-containing media. The results obtained support predicted vital roles of several residues for enzymatic activity and led to the identification of residues indispensable for the MMS-sensitizing effect. Despite an overlap between these two properties, careful analysis revealed two mutations, Asn75 and His324, which decouple the enzymatic activity and the MMS-sensitizing effect, indicating two distinctive biological activities linked in this key gluconeogenesis enzyme.